Nowa Republika . miesięcznik polityczny, no. 3, 1984 - Ruch Społeczny "Solidarność", [ed. Jan Kosiński, Marek Woliński] (s.n.], 1984)
Creation and circulation: Publication with reviews of periodicals and books in underground circulation. From no. 23(1988) publication is part of the Koordynacja Wydawnicza at RKW NSZZ "Solidarność" Region Dolny Śląsk